2021
DOI: 10.3389/fcvm.2021.706979
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Thrombus Aspiration and Interaction With D-Dimer Levels in Patients With ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: Objectives: To evaluate the effect of thrombus aspiration (TA) strategy on the outcomes and its interaction with D-dimer levels in patients with ST-segment elevation myocardial infarction (STEMI) during primary percutaneous coronary intervention (PCI) in “real-world” settings.Materials and Methods: This study included 1,295 patients with STEMI who had undergone primary PCI with or without TA between January 2013 and June 2017. Patients were first divided into a TA+PCI group and a PCI-only group, and the baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It also has a serious importance on the prognosis after MI (in-hospital death, Q-wave myocardial infarction, urgent or emergent coronary artery bypass surgery and stroke). [18][19][20] MPV elevation, which is a marker of platelet function, is associated with an increased risk of cardiovascular diseases such as myocardial infarction, stroke and transient ischemic attack. In their study, Han et al showed that the incidence of stroke and coronary artery disease was higher in the group with MPV>8 fL.…”
Section: Discussionmentioning
confidence: 99%
“…It also has a serious importance on the prognosis after MI (in-hospital death, Q-wave myocardial infarction, urgent or emergent coronary artery bypass surgery and stroke). [18][19][20] MPV elevation, which is a marker of platelet function, is associated with an increased risk of cardiovascular diseases such as myocardial infarction, stroke and transient ischemic attack. In their study, Han et al showed that the incidence of stroke and coronary artery disease was higher in the group with MPV>8 fL.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the complex calculation of ACCI based on medical history, D-dimer could be identified only by a blood test, which might be more suitable for patients with critical illnesses or speech disorders. In a real-world retrospective study, Li et al ( 10 ) observed that patients with STEMI who had a higher plasma D-dimer might benefit from the use of thrombus aspiration during primary PCI. In addition, we used joint indicators to predict MACEs and all-cause deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that increased D-dimer levels are associated with the presence and severity of coronary disease (6)(7)(8) and indicate an unfavorable prognosis for stable coronary disease (9). Therefore, D-dimer may be a valuable marker for predicting ischemic events (10). However, to our knowledge, the role of D-dimer in predicting the incidence of adverse events in Chinese patients with non-ST-segment elevation myocardial infarction (NSTEMI) has not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%